2000
DOI: 10.1037/0022-0663.92.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral student experiences in gender-balanced and male-dominated graduate programs.

Abstract: Similarities and differences were examined in graduate school experiences of male and female doctoral students in programs containing predominantly male or gender-balanced faculty. Participating students reported their perceptions of mentor support, partner support, peer support, academic self-concept, sensitivity to family issues, stress, and career commitment. In studies, women in male-dominated programs expressed lower academic self-concept, less sensitivity in their departments to family issues, and lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 33 publications
4
63
0
Order By: Relevance
“…2 Experimental work by Gneezy et al (2003) shows that women are less effective than men in competitive environments, although no significant gender differences are observed in noncompetitive environments. These experimental findings are perfectly in line with survey results obtained by Ülkü-Steiner et al (2000) on 341 doctoral students that "women in male-dominated programs expressed lower academic self-concept, (…) and lower career commitment compared with all other students" (p.296).…”
Section: Introductionsupporting
confidence: 80%
“…2 Experimental work by Gneezy et al (2003) shows that women are less effective than men in competitive environments, although no significant gender differences are observed in noncompetitive environments. These experimental findings are perfectly in line with survey results obtained by Ülkü-Steiner et al (2000) on 341 doctoral students that "women in male-dominated programs expressed lower academic self-concept, (…) and lower career commitment compared with all other students" (p.296).…”
Section: Introductionsupporting
confidence: 80%
“…For female students, university STEM programs are particularly "gendered organizations" given the high proportion of males in high-ranking positions (Britton et al 2012;Fox et al 2011;White and Ivie 2013), especially at the graduate level where the proportion of female students and faculty drops (White and Ivie 2013). Female doctoral students, even after already demonstrating competence as undergraduates, experience lower academic self-concept and low career commitment in male-dominated environments that lack mentor support and reflect insensitivity to family issues (Ülkü-Steiner et al 2000). They perceive others as doubting whether their accomplishments are due to advantaged treatment rather than merit, while attributing their failures to individual deficiencies.…”
Section: The Gendered Culture Of Stem Graduate Educationmentioning
confidence: 99%
“…Ülkü-Steiner, Kurtz-Costes, and Kinlaw (2000) found that it was the presence of female faculty in a department and not the gender of the student's mentor that is most important for enhancing doctoral students' academic experience in male-dominated graduate programs. The number of women faculty mentors in the IT programs surveyed in this study is highly outnumbered by males.…”
Section: Discussionmentioning
confidence: 99%